Comparative Analysis of Anthropometric Characteristics between Athlets of Different Orientation, Basketball and Handball - Marina Vukotic; Georgi Georgijev (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The main goal of this research is to determine whether there are statistically signifi cant diff erences in the level of anthropometric indicators among athletes of diff erent sports directions (basketball and handball players), that is, to determine the diff erences in the changes in the anthropometric indicators of athletes. In accordance with the goal, a transversal study was conducted in which the empirical and statistical methods were applied, and the research technique was testing. The study was conducted on a sample of 50 subjects, a male gender divided into two subunits, an age range of 13 to 15 years. In this study, 12 anthropometric variables were tested: body height, arm length, leg length, knee diameter, bicrystalline range, bichromium range, body mass, median volume of the thorax, circumference, upper abdomen, skin abdomen and skin set of lower legs. For all applied variables, the central and dispersion parameters as well as measures of asymmetry and fl attening were calculated, and the distribution normality was verifi ed by Kolmogorov-Smirnov test. T-test was applied to verify that the system of applied variables has statistically quantitative diff erences between groups. On the basis of the obtained results, it can be concluded that there are statistically signifi - cant diff erences in anthropometric indicators in athletes of diff erent sports orientations. This research can be used by trainers who realize training programs with these and other athletes in order to achieve better results.